A Handling Study to Assess the Use of the Respimat® Soft Mist™ Inhaler in Children Aged 4–12 Years. Issue 1 (December 2015) - Kamin, Wolfgang; Krackhardt, David; Gössl, Rüdiger; Kattenbeck, Sabine; Koker, Paul; Moroni-Zentgraf, Petra; Wachtel, Herbert
Abstract Introduction The Respimat® Soft Mist™ Inhaler (SMI) is a hand-held device that generates an aerosol with a high fine-particle fraction, enabling efficient lung deposition. Inhalation therapy for children should be safe and effective. This study aimed to assess the success and the quality of inhalation maneuvers among children using the Respimat SMI. Methods This single-center study was conducted at Mainz University Hospital, Germany, between March 2006 and August 2006. Ninety-nine children, aged 4–12 years, with asthma bronchiale or other atopic diseases, and their healthy siblings were included. Children with serious respiratory conditions such as cystic fibrosis or any chronic destructive or severe lung disease were excluded. Each child performed three inhalation maneuvers using the Respimat SMI. Inspiratory flow rate, inhaled volume, and timing of actuation for each inhalation maneuver were recorded using a pneumotachograph. Successful use and quality of inhalation maneuvers (inspiratory flow rate, theoretical inhaled dose fraction, and estimated lung deposition of the aerosol cloud) were assessed. Results were compared with respect to prior experience of inhaler use and between two age groups (4–8 years and 9–12 years). Results Ninety of 99 children achieved one or more successful maneuver. Overall, 75.1 % of inhalation maneuvers performed with the Respimat SMI were successful; the greatest success was seen in older versus younger children. Overall median estimated lung deposition was 67 %. Median inspiratory flow was 41.5 L/min, with slower rates noted in the younger children. Fifty-two percent of children inhaled faster than 40.0 L/min. Prior inhaler experience imparted no benefit in terms of success of inhalation maneuvers, overall, but was associated with some group differences in inhalation flow rate. Conclusion Children can perform a successful inhalation maneuver with the Respimat SMI, with the greatest success rate in children aged >5 years.